KEANEKARAGAMAN JENIS MERANTI (SHORE SPP) PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KABUPATEN KUBU RAYA PROPINSI KALIMANTAN BARAT - HB, Irwan; Manurung, Togar Fernando; Herawatiningsih, Ratna (Universitas Tanjungpura, 2015)
The purpose of this study was to obtain data and information about of the diversity of meranti (Shorea spp) on Forest Area Ambawang Mountain, Kubu Raya Districts, West Borneo, in the area of the Protected Forest Mount Ambawang accurately and reliable, it necessary selected the proper method is to plot Double Squares method. The results showed that in the area of Protected Forest Mount Ambawang found 23 specie's of trees making forest stands for all levels of forest stands located at 20 observation plots with a total area of 3.2 hectares observations. From 23 species found there were four types of meranti includ meranti Batu (S. uliginosa), meranti Bunga (S. parvifolia), meranti padi (S. ovata) and meranti saranglang (Shorea spp), 4 meranti found in the area of Protected Forest Mount Ambawang are included in the group of meranti merah. Keyword : diversity, protectedÂ forest.